The Word become Flesh. Wild orality and “palliative” conservation for the Mexican performative arts - Juan Gerardo Ugalde Salinas (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Since the beginning of the twentieth century, Mexico's political and social context has influenced a body of performance artworks rich in activist connotations, full of black humor and references to the violence and injustice surrounding. How do we, conservators, find ourselves implicated in these dynamics that involve creativity and sensibility arising in the face of chance of collective memory? This text revisits some considerations on the treatment and conservation of these very specific works, decanted to the movements of Latin American artistic autonomy, and which in a consensus between specialists and artists, may find in orality and “assisted” disappearance a chance to ensure their perpetuity.